2022
DOI: 10.1136/tobaccocontrol-2021-056986
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mainstream emissions, secondhand emissions and the environmental impact of IQOS waste: a systematic review on IQOS that accounts for data source

Abstract: ObjectiveTo highlight the general features of IQOS literature focusing on the chemical analysis of IQOS emissions.Data sourcesPubMed, Web of Science and Scopus databases were searched on 8 November 2021 using the terms ‘heated tobacco product’, ‘heat-not-burn’, ‘IQOS’ and ‘tobacco heating system’ with time restriction (2010–2021). The search yielded 5480 records.Study selectionRelevant publications on topics related to IQOS assessment were retrieved (n=341). Two reviewers worked separately and reached agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 120 publications
0
25
1
Order By: Relevance
“…Such finding is in line with the results of previous studies that reported similar nicotine levels in the emissions of differently flavored HEETS. 5 , 7 , 35 However, we detected slightly lower levels of nicotine in HEETS emissions compared with previous studies, likely due to the different amount of puffs (10 in our study, 12 in previous investigations) taken per HEET. 5 , 12 …”
Section: Discussioncontrasting
confidence: 80%
“…Such finding is in line with the results of previous studies that reported similar nicotine levels in the emissions of differently flavored HEETS. 5 , 7 , 35 However, we detected slightly lower levels of nicotine in HEETS emissions compared with previous studies, likely due to the different amount of puffs (10 in our study, 12 in previous investigations) taken per HEET. 5 , 12 …”
Section: Discussioncontrasting
confidence: 80%
“…Puffing regimes affect the combustion or heating of tobacco ingredients (or e-liquids for ECs) leading to different mechanisms of thermal degradation, and hence different profiles of emissions. , Standard puffing regimes like the International Standardization Organization (ISO) and Health Canada Intense (HCI) are used to characterize tobacco product emissions for regulatory purposes; however, they were recently shown to be not representative of the topography of actual smokers in natural environments . These cigarette standards are also not suitable for other tobacco products, especially ATPs . Also, the CORESTA regime used for ECs does not represent the actual use of the wide variety of available ECs .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to combustible cigarettes, ATPs have different modes of operation, composition, and emission profiles. While cigarettes deliver nicotine to the user by combusting tobacco, HTPs do so by electrically heating a tobacco filler, and ECs do so by vaporizing a nicotine-containing liquid on an electrically heated coil. , The differences in how devices produce the nicotine aerosol can lead to differences in the chemical profile of their emissions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations